Inorganic Geochemistry of Coal from Patappa Village, Bone District, and Masenrengpulu Village, Barru District, South Sulawesi Province Using XRF Method - Anshariah, Anshariah; Thamsi, Alam Budiman; Tholib, Mohammad (Universitas Sanata Dharma, 2024)
The chemical composition of coal is almost the same as that of plant tissue, containing the main elements of elements C, H, O, N, S, and P. An in-depth study of coal inorganic compounds is needed because coal inorganic compounds are the primary variable in ash formation during coal combustion. This study uses the X-ray fluorescence method to reveal the differences and similarities in inorganic chemical composition contained in coal in Bone Regency and Barru Regency. Coal in Masenrengpulu Village has the Al2O3 compound as the most dominant compound, while coal in Patappa Village has the SiO2 compound as the most prevalent compound. The concentration of inorganic sulfide minerals in the village of Masenrengpulu was influenced by igneous rock intrusion and deposition processes. In contrast, the deposition process only affected the inorganic sulfide minerals of coal in Patappa village. The significant elements found in coal in the Masenrengpulu and Patappa Villages are Si, Al, Fe, S, Ca, K, and Ti. Coal inorganic sulfide minerals in Masenrengpulu Village with Patappa Village have high concentrations in the bottom channel of the coal seam and a low concentration in the middle channel and top of the seam. Coal inorganic sulfide minerals in Masenrengpulu Village and Patappa Village have high concentrations in the coal seam's lower channel and low concentrations in the middle and upper channels. Keywords: Coal Comparison, Mallawa Formation, XRF, Inorganic Geochemistry.